The Influence of Competence, Organizational Culture, and Work Motivation on Employee Performance at PT. Hibaindo Armada - Samroh (SAJMR : Southeast Asian Journal of Management and Research, 2024)
This study aims to analyze the influence of competence, organizational culture, and work motivation on employee performance at PT. Hibaindo Armada. Employee competence, as an individual's ability to effectively carry out tasks, is seen as a key factor affecting performance. Additionally, a strong organizational culture can positively impact employee morale and behavior, thereby increasing productivity. Work motivation also plays a crucial role in driving employees to achieve the company's targets. Using a quantitative method, this research is expected to provide an overview of the relationships between these factors and offer recommendations that the company can implement to improve overall employee performance.